Combined Activity In Vitro of Caspofungin, Amphotericin B, and Azole Agents against Itraconazole-Resistant Clinical Isolates of Aspergillus fumigatus - Cuenca-Estrella, Manuel (American Society for Microbiology, 2005)
Interactions in vitro between amphotericin B, itraconazole, voriconazole, and caspofungin against itraconazole-resistant Aspergillus fumigatus clinical strains were determined. Differential results were obtained depending on the criteria (MIC or minimal effective concentration) used. Caspofungin and voriconazole exhibited the most potent interactions, with synergy against at least 50% of isolates, and the average fractional concentration index was 0.38. Antagonism was not found for any combination.